Teaching the Female Breast and Pelvic Exam: A Student- and Patient-Centered Approach - Erin L. Nelson (Association of American Medical Colleges, 2016)
Abstract Introduction Breast and pelvic examinations are an important part of the complete physical examination of a female patient. Unfortunately, performing this type of exam may be anxiety- or fear-provoking for the novice learner. These areas of the body are sensitive, and a student's own lack of knowledge, confidence, and experience in performing these types of examinations adds to the challenge of teaching these skills. Methods This resource was developed for second-year medical students and consists of background reading, a video, and two hands-on sessions to facilitate learning. Depending on the number of learners, the lab can be completed in one afternoon session. The appended materials include a facilitator guide, student instructions, and video demonstrations of the female breast and pelvic exams. Results A review of 4 years of session evaluation data (n = 866 students) revealed high levels of student satisfaction (97.9%) and improved levels of student confidence (95.6%) following the session. Discussion This material could be useful for learners in both undergraduate and graduate health professions training, including nurse practitioners, nurse midwifes, medical students, and interns in the fields of obstetrics and gynecology, family medicine, or internal medicine.